O jornal e o jornalista de amanhã - Costa, Luciano Martins (1998)
The article emphasizes the importance of the newspaper, as a company, and of the journalist, as a professional, being aware of the challenges which appear and also of the resulting search for new mana-gement methods and processes. Furthermore, it stresses the importance that regional journalism has taken on and the need for this practice to turn itself more to the community, to education and, therefore, to extrapolating the view one has of the reader as a mere information consumer, to see him as a citizen, a partner in the elaboration and reflection on the facts that are transmitted.